Proyecto de factibilidad para la creación de una microempresa de servicios de alquiler de vehículos, en la ciudad de Zamora, cantón Zamora, provincia de Zamora Chinchipe, para el año 2016 - González Novillo, Darío David (2017)
he present investigation has as concrete aim, know the feasibility for the creation of one mike company of services of rent of vehicles, in the city of Zamora, canton Zamora of the province of Zamora Chinchipe, for the year 2016, by means of a services of excellent quality across a programmed and opportune efficiency, which satisfies the needs of the inhabitants of the canton Zamora. For this reason the work investigative initial Economic Partner of Zamora treats on the analysis, for which I work with a population PEA of 24.951 men and 11.090 Women, with a total of 36041 persons, and in agreement to the formula I apply 380 surveys to him to the PEA, in the second part the Market research is realized, defining hereby the offer and the demand of the service of rent of vehicles. Administrative officer, Organizacional and Legal in which the creation of a company was defined in the modality of Limited Responsibility, for which establishes the flowcharts for the company with the respective functions of every area, determining this way the Economic Financial Study, in which Financier elaborates the States to know his royal feasibility, Finally I determine the economic Evaluation determining a positive rate of the discount and the indexes of profitability, and Environmental Impact of the Project, Finally to there have been elaborated his respective conclusions and recommendations that constitute the final evaluation of the project, with which there is demonstrated that in any area the creation of the micro is feasible company of rent of vehicles in the city of Zamora, for the year 2016.